CXCL13 as a new biomarker of systemic lupus erythematosus and lupus nephritis – from bench to bedside?. (January 2015) - Schiffer, L.; Worthmann, K.; Haller, H.; Schiffer, M.
Summary Different studies over the last decade have linked the B cell‐attracting chemokine CXC ligand 13 (CXCL13) to the autoimmune disease systemic lupus erythematosus (SLE). A pathogenetic role of this chemokine for disease manifestation in SLE was described initially in mouse models for SLE. Mechanisms of CXCL13 actions were also identified in SLE patients. Moreover, various clinical studies have identified CXCL13 serum levels as a useful biomarker in patients with SLE of different ethnicities for disease activity. In addition, CXCL13 seems to be a promising marker for the diagnosis of lupus nephritis, one of the most severe complications of SLE. However, its exact place within the mechanisms that lead to SLE remains to be defined. Further research is needed to resolve more details of the pathomechanism and the signalling pathway of CXCL13 in SLE. Blocking CXCL13 or the signal pathways of CXCL13 is seen as a promising therapeutic approach for SLE and will be addressed in the near future. This review summarizes all papers that linked CXCL13 to SLE and highlights its importance in the pathogenesis and diagnosis of SLE